Literasi Keuangan, Financial Planning Dan Financial Behavior: Faktor Penentu Keputusan Investasi Generasi Z Di Denpasar - Putu Pande R. Aprilyani Dewi; Budiadnyani, Ni Putu; Frinabila , Anastasya (Politeknik Negeri Ambon, 2024)
The capital market investment decisions of Generation Z in Denpasar City reflect the unique dynamics of a demographic group that is increasingly playing an important role in the local economy. Generation Z, known as the digital native generation, has extensive access to information and technology that influences the way they invest. Denpasar City, with its rapid economic growth and growing Generation Z population, offers both opportunities and challenges for young investors to make investment decisions, including the factors that influence those decisions, which can provide valuable insights for designing more effective financial education programmes and investment strategies. A key factor influencing investment decisions is financial literacy knowledge, which plays an important role in determining how effectively Generation Z can make investment decisions. The population in this study is members of Generation Z who live in Denpasar City. The sample determination used purposive sampling technique, where the sample was randomly selected based on certain criteria or restrictions set by the researcher, where because the population size was not known with certainty, the formula from Hair et al was used for determining the sample. The results of this study are financial literacy, financial planning and financial behaviour affect the investment decisions of generation z in Denpasar City. Â Keyword: nvestment decision, financial literacy, financial planning, financial behaviour